المجاز فى قصيدة "الحب بلا حدود" لنزار قباني: Metaphor in the poem" Love Without Borders " by Nizar Kabbani - Eni Zulfa Hidayah (MUHIBBUL ARABIYAH: Jurnal Pendidikan Bahasa Arab, 2022)
This study discusses about the metaphor in Qasidah al Hubb bila hudud written by Nizar Qabbani, a contemporary poet from Syria. He has many literary works. One of which is a poem / qasidah with the title Qasidah al Hubb Bila Hudud. The choice of phonemes and words strung together in a poem with its beauty both in terms of sentences and meanings which are enriched with the privilege of the message within to express his love for his lover which is then conveyed through some interesting metaphors to study. And the theory used by the researcher is Ullman's theory involves anthropomorphic metaphors, metaphors from concrete to abstract, and synesthetic metaphors. The approach used by the researcher is qualitative descriptive with the type of research literature study. The Data were collected from document review and the data analysis using content analysis method. The data in this study is the metaphor in Qasida al Hub Bila Hudud by Nizar Qabbani. The results of this study show that there are three types of metaphors in Qasidah al Hubb Bila Hudud, namely anthropomorphic metaphor, metaphor from concrete to abstract, and synesthetic metaphor. The message that the poet wanted to convey from his poem in some verses, “You will always appear in my eyelids like a flock of doves, and the kind of feeling will never change in my heart, in my mind, in my body, in my belief, so I will use all of those as a bridge to reach my religion." It shows that how much we love someone we should make it as a means to achieve the love and will of the Almighty owner of the love, Allah SWT.